circHIPK3 regulates lung fibroblast-to-myofibroblast transition by functioning as a competing endogenous RNA - Zhang, Jia-xiang; Lu, Jian; Xie, Hui; Wang, Da-peng; Ni, Huan-er; Zhu, Yong; Ren, Le-hao; Meng, Xiao-xiao; Wang, Rui-lan (Cell death & disease, 2019)
Myofibroblasts predominantly emerging through fibroblast-to-myofibroblast transition (FMT) are considered to be the key collagen-producing cells in pulmonary fibrosis. Circular RNAs (circRNAs) are important players involved in many biological processes. circHIPK3 has been identified as the one of the most abundant circRNAs in human lung. In this study, we characterized the role of circHIPK3 in pulmonary fibrosis. We revealed that circHIPK3 is upregulated in bleomycin-induced pulmonary fibrosis mice model, FMT-derived myofibroblasts. circHIPK3 silencing can ameliorate FMT and suppress fibroblast proliferation in vivo and vitro. Fundamentally, circHIPK3 regulates FMT by functioning as an endogenous miR-338-3p sponge and inhibit miR-338-3p activity, thereby leading to increased SOX4 and COL1A1 expression. Moreover, dysregulated circHIPK3 expression was detected in the clinical samples of patients with idiopathic pulmonary fibrosis. Intervention of circHIPK3 may represent a promising therapy for pulmonary fibrosis.